Immortalized HEK 293 Kidney Cell Lines as Models of Renal Cells: Friends or Foes? - Cesare Achilli; Annarita Ciana; Giampaolo Minetti (Journal of Controversies in Biomedical Research, 2018)
The immortalized cell lines derived from human embryonic kidney, named HEK 293, are extensively used as models of human renal cells in in vitro studies. Nevertheless, ample evidence in the literature shows that HEK 293 cells display genotypic and phenotypic characteristics that differ substantially from primary kidney cells, with potential detrimental effects on the quality of the experimental results. Among the differences documented between HEK 293 and renal cells, there is an altered pattern of expression of many proteins involved in the development and physiological functions of the kidney. Methionine sulfoxide reductase (Msr) enzymes are ubiquitous components of the cellular machinery, evolved to counteract the damages inflicted to methionine residues by oxidative stress, particularly intense in kidney tissues. In this article, we have compared the levels of expression of several different Msr enzymes in human kidney and in a HEK 293 strain and have observed significant differences between the two cell types.